Tumor Lysis Syndrome in a Patient With Gastric Adenocarcinoma. (June 2020) - Lingamaneni, Prasanth; Desai, Parth; Vennikandam, Madhu Mathew; Moturi, Krishna; Baranwal, Anmol; Gupta, Shweta
Tumor lysis syndrome (TLS) is a severe metabolic complication that usually occurs in patients with aggressive tumors who undergo treatment with chemotherapy. Traditionally, it was mainly associated with hematologic malignancies. However, over the past 4 decades, there have been increasing reports of TLS in solid tumors. We report a case of TLS in a patient with gastric cancer, as a complication of FOLFOX (5-fluorouracil, leucovorin, and oxaliplatin) chemotherapy. Our patient was a 48-year-old man with metastatic gastric adenocarcinoma who presented with altered mental status and slurred speech. On examination, he was confused and disoriented, but the rest of his examination, including vitals, was unremarkable. Laboratory findings on admission were significant for an elevated uric acid of 14.5 mg/dL, creatinine of 4.1 mg/dL, and phosphorus of 6.9 mg/dL. He had received his first cycle of FOLFOX chemotherapy 4 days prior to admission. The constellation of electrolyte abnormalities and the temporal relationship to chemotherapy led to the diagnosis of chemotherapy-induced TLS. He was treated with aggressive fluid repletion and rasburicase, following which the electrolyte derangements resolved, and he improved clinically. This case highlights the importance of early recognition of TLS in patients with gastric cancer. Initiation of early treatment can reduce the high morbidity and mortality associated with this oncologic emergency.